1975
DOI: 10.2307/3897488
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and Reservoir Quality for Livestock Use in Southeastern Montana

Abstract: The study was conducted on rangelands in the Pierre Shale TDS) and were rated good to fair for livestock use, However, Plains and Badlands Land Resource Area of Carter County in as water levels drop, mainly through evaporation, waters in southeastern Montana. The fine-textured, panspot, saline-sodic some reservoirs could become moderately saline (3,000 to soils in this area have low infiltration rates (less than 1 10,000 mglliter of TDS) and should not be used if other cm/hour) and are sparsely vegetated (Fig.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Blue grama (Bouteloua gracilis), buffalograss (Buchloe dactyloides), and clubmoss (Selaginella densa) dominated small residual pedestals of coarse-textured material. On the saline-upland range site, alkali sacaton (Sporobo- (Soiseth 1975) from water samples collected during a study in the same general geographic area in 1971-1973. Samples were collected from all of the unfurrowed watersheds, but only two of the furrowed watersheds produced runoff, because rainfall during this period of record did not exceed the furrow water storage capacity on the other three furrowed watersheds during any single storm.…”
Section: Site Description and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blue grama (Bouteloua gracilis), buffalograss (Buchloe dactyloides), and clubmoss (Selaginella densa) dominated small residual pedestals of coarse-textured material. On the saline-upland range site, alkali sacaton (Sporobo- (Soiseth 1975) from water samples collected during a study in the same general geographic area in 1971-1973. Samples were collected from all of the unfurrowed watersheds, but only two of the furrowed watersheds produced runoff, because rainfall during this period of record did not exceed the furrow water storage capacity on the other three furrowed watersheds during any single storm.…”
Section: Site Description and Methodsmentioning
confidence: 99%
“…Most previous investigations have studied quantity rather than quality of stock water supplies, but Soiseth (1975) reported that runoff and reservoir water quality in southeastern Montana was good to fair, and that the chemical quality of water stored in ponds could deteriorate to poor during the grazing season as water levels decrease by evaporation. The objective of the study reported here was to assess the chemical quality and sediment content of runoff water from finetextured rangeland soil in southeastern Montana.…”
mentioning
confidence: 99%
“…Specific conductivity (SC), which is easy to measure, can be converted to approximate TDS. Soiseth (1975) reported that for southeastern Montana TDS = 0.819 (SC) -86.9; the results of this study indicated TDS q 1 .Ol (SC) -299, (Rr = 0.95). Because of the high TDS levels reported for some surface mine impoundments, these waters should be tested before they are used for livestock.…”
Section: Discussionmentioning
confidence: 39%
“…Depth of 0.5% light penetration was used as an indicator of turbidity in this study. Turbidity in livestock waters is in itself not generally a problem, although livestock could conceivably be affected by drinking muddy water (Soiseth 1975). Bentonite surface mine impoundments were the most turbid, although all 3 types included some impoundments that were very turbid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation